Paraproteinaemic Neuropathies - Steck, Andreas J. (Brain Pathol, 2006)
In this article, we review the main clinical and pathological features of paraproteinaemic neuropathies and discuss recent experimental findings. Further knowledge of the disease process at the molecular level has allowed a better characterization of clinical syndromes and has given new insights into their pathogenesis. The most convincing evidence for a causal relationship can be drawn from IgM monoclonal gammopathies with specificities directed against carbohydrate determinants of the myelin associated glycoprotein (MAG). There remain however, many unresolved questions, such as how monoclonal anti‐MAG IgM antibodies cross the blood‐nerve barrier and trigger a chronic demyelinating polyneuropathy while the central nervous system is essentially spared. IgM paraproteins with specificity for other molecules, such as neurofilaments, sulphatide, gangliosides, chondroitin sulphate and tubulin, have also been identified, but their pathogenetic importance remains to be elucidated. Other paraproteinaemic neuropathies such as IgG and IgA neuropathies have to be considered separately. The paraneoplastic endocrine and cytokine manifestations of rare osteosclerotic myelomas provide valuable insights into the interaction between the immune and the nervous system. The antigen‐specificity of IgG and IgA monoclonal antibodies are only poorly characterized but some have been found to be directed against endoneurial determinants and a few against axonal proteins such as neurofilaments.